Serum selenium, selenoprotein P and glutathione peroxidase 3 in rheumatoid, psoriatic, juvenile idiopathic arthritis, and osteoarthritis - Wahl, Lukas; Samson Chillon, Thilo; Seemann, Petra; Ohrndorf, Sarah; Ochwadt, Ragna; Becker, Wolfgang; Schomburg, Lutz; Hoff, Paula (The Journal of nutritional biochemistry, 2025)
•The majority of patients with iRMD exhibit a selenium and selenoprotein deficiency.•Selenoprotein P correlates with the functional status of osteoarthritis patients.•Elevation of Selenoprotein P may improve functional impairment in Irmd. Selenoprotein P (SELENOP) controls selenium (Se) transport, and glutathione peroxidase 3 (GPx3) elicits antioxidant activity in blood. Inflammation associates with Se deficiency, but knowledge concerning selenoproteins in inflammatory rheumatic musculoskeletal diseases (iRMD) is limited. We compared three Se biomarkers in patients with rheumatoid (RA), psoriatic (PsA), and juvenile idiopathic arthritis (JIA) in comparison to osteoarthritis (OA) and healthy subjects, to improve the data base on selenoprotein expression in iRMD. The cross-sectional study enrolled n=272 patients with RA (n=131), PsA (n=67), JIA (n=22) and OA (n=52). Serum Se was quantified by total reflection X-ray fluorescence, SELENOP by ELISA and GPx3 by an enzymatic test. Data from the EPIC trial served as reference. Impairment of daily life was assessed by the Functional Ability Questionnaire (FfbH). Serum SELENOP and Se concentrations correlated linearly in all groups and were below the average measured in EPIC. Se concentration was not different between the patient groups. Compared to controls, SELENOP levels were low in iRMD patients. GPx3 activity was particularly low in JIA and PsA. Seropositive but not seronegative RA patients displayed a disrupted interaction between GPx3 and Se or SELENOP. SELENOP associated with the functional status measured by the FfbH, most pronounced in OA (R=0.76, P < .01). The data indicate selenoprotein deficiency in the majority of patients with iRMD, and a positive relation of SELENOP with functional status in OA. Since increased Se supply improves selenoprotein biosynthesis, a personalized correction of diagnosed deficiency merits consideration to improve Se transport and ameliorate disease burden.